Descriptive Analysis of User Satisfaction with SIANIS Application Services in Higher Education Environments - Iis Sumandari; Tamrin Tamrin; Katriza Katriza (JURNAL ECONOMINA, 2026)
his study aims to comprehensively evaluate the level of user satisfaction with the Non-Inventory Expendable Asset Information System (SIANIS) implemented at the Faculty of Teacher Training and Education, Sriwijaya University by reviewing the quality of electronic services provided through the system. This study is motivated by the increasing importance of implementing a digital-based asset management system in supporting administrative efficiency, transparency, and accuracy of data management in higher education environments. The study uses a descriptive quantitative approach involving 50 respondents consisting of students and laboratory administrative staff who actively use the SIANIS application in academic and administrative activities. Data collection was carried out through the distribution of structured questionnaires using a five-point Likert scale, while data analysis was carried out using descriptive statistical techniques based on the e-Servqual framework which includes seven dimensions, namely efficiency, system availability, fulfillment, privacy, responsiveness, compensation, and contact. The results of the study indicate that the overall level of user satisfaction with the SIANIS application is in the "satisfied" category with an average value of 3.60, which indicates that the system has been able to meet user expectations in supporting the process of managing non- inventory expendable assets. Specifically, the efficiency, system availability, fulfillment, and compensation dimensions received positive ratings, indicating that the application is capable of providing easily accessible, functional, and fairly reliable services to users. However, several other dimensions, particularly privacy, responsiveness, and contact, received relatively lower scores and were in the "quite satisfied" category, indicating limitations in user data protection, speed of technical service response, and effectiveness of communication between system administrators and users. This study concludes that although the SIANIS application has made a positive contribution to improving the quality of digital-based administrative and asset management services within the faculty environment, system optimization still needs to be carried out to increase user trust, strengthen service responsiveness, and develop more interactive communication features. The results of this study are expected to serve as evaluation material and considerations for policymakers and system developers in designing digital service innovations that are more oriented to user needs in the higher education administration environment